Saber hacer y tradición en La Chamba, Colombia: un estudio etnográfico de la selección de arcillas - Angela María Cadena Muñoz (Bulletin de l'Institut Français d'Études Andines, 2020)
The selection of raw materials for the elaboration of ceramic artifacts is relevant to understand the relationship between potters and clay through their social representations and to avoid interpretative biases in archaeological analyses of the factors that influence the decision of potters in the acquisition of clay. Through an ethnographic study involving an analysis of narratives and material culture, the technical decisions for clay extraction made by five potters from La Chamba (Southwestern Colombia) are described. This study shows that rather than environmental factors, raw material, selection decisions are mediated by savoir faire and tradition.